2015
DOI: 10.1155/2015/659150
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Surgical Management of Duodenal Duplication in Adults

Abstract: Duodenal duplications in adults are exceedingly rare and their diagnosis remains difficult as symptoms are largely nonspecific. Clinical presentations include pancreatitis, biliary obstruction, gastrointestinal bleeding from ectopic gastric mucosa, and malignancy. A case of duodenal duplication in a 59-year-old female is presented, and her treatment course is reviewed with description of combined surgical and endoscopic approach to repair, along with a review of historic and current recommendations for managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…Cuando el quiste compromete la cabeza del páncreas, se recomienda la realización de una pancreatoduodenectomía 3 ; en estos casos, la derivación por cistoyeyunostomía puede dar lugar a una resolución incompleta debido a la presencia de mucosa heterotópica, con el consiguiente riesgo de ulceración, perforación y desarrollo de malignidad, como ha sido informado 7,20 .…”
Section: Discussionunclassified
“…Cuando el quiste compromete la cabeza del páncreas, se recomienda la realización de una pancreatoduodenectomía 3 ; en estos casos, la derivación por cistoyeyunostomía puede dar lugar a una resolución incompleta debido a la presencia de mucosa heterotópica, con el consiguiente riesgo de ulceración, perforación y desarrollo de malignidad, como ha sido informado 7,20 .…”
Section: Discussionunclassified
“…A previous review described 96 patients with tract duplication over a 37-year period and found no evidence of tubular duodenal duplications; rather, all duodenal duplications were cystic malformations ( 11 ). Furthermore, only a few cases of tubular duodenal duplication or intraluminal duodenal diverticulum have been reported in elderly women ( 13 , 14 ). Our case was unusual and involved a diverticular and communicating type, which we referred to as an IDDD; this is the first documented instance of a giant IDDD in a child.…”
Section: Discussionmentioning
confidence: 99%
“…They have diverse clinical manifestations depending in the location, the presence or not of complications and the relationship with adjacent organ especially the pancreas and the biliary tree. Recurrent nausea, vomiting, abdominal mass, pancreatitis, jaundice can be seen [5][6][7][8][9][10]. In the systematic review of Chen et al compiling 47 cases of DD cysts, 80% of patients presented with abdominal pain and only 18 patients were older than 20 years [1].…”
Section: Discussionmentioning
confidence: 99%